Peran perpustakaan madrasah dalam memajukan program literacy di lembaga pendidikan ke-Islaman - Mahfudz A. Junaidy (Al Maktabah, 2007)
Madrasa is one of the institution of the Islamic education which has big role in promoting literacy program., like Madrasa Nasriyah in Masjid ai-Aqsa. Madrasa Nasriyah also known as Madrasa AI-Ghazaliyah as a honor of Imam Gazali. He has finished his work there namely Book lhya al-'Ulum al-Din. We agree that every madrasa has library, and we call madrasa library. Key Words: Perpustakaan Madrasah, Lembaga Pendidikan, Literacy.